Ciência agrícola - Universidade Federal de Alagoas. Centro de Ciências Agrarias (Centro de Ciências Agrarias da Universidade Federal de Alagoas, 1991)
Focused on research in forestry engineering, soil sciences, plant protection, agricultural engineering, plant production, and animal production.
Keywords: Agriculture : Periodicals; Agriculture